Direct oral anticoagulants: an alternative treatment for thrombotic antiphospholipid syndrome?. (October 2017) - Resseguier, A S; Pereira, B; Rieu, V; Le Guenno, G; Grobost, V; Ruivard, M
Background: Direct oral anticoagulants (DOACs) demonstrate a lower risk–benefit ratio than vitamin K antagonists (VKAs) for secondary thromboprophylaxis of thrombotic events. But there are no data on the efficacy of DOACs for the prevention of thrombotic recurrence in patients with antiphospholipid syndrome (APS). In this study, we evaluated the efficacy of DOACs to prevent recurrences of thrombotic events in patients with APS. Methods: This was a single-center pilot, using a multi-step Fleming design. If seven or fewer patients presented treatment failure with rivaroxaban, the study could conclude efficacy. Results: A total of 23 patients were included. APS involved the veins only ( n  = 19), arteries only ( n  = 2) or both ( n  = 1) and 1 patient exhibited catastrophic antiphospholipid syndrome (CAPS). Overall, two patients were positive for lupus anticoagulant, anti-beta-2 glycoprotein I antibodies and anticardiolipid antibodies (triple positivity). The mean duration of follow up was 35.6 (range, 29–40) months. A total of six treatment failures were reported: one patient, with triple positivity, developed bilateral distal pulmonary embolism (PE) after 20 months of treatment with rivaroxaban, two patients refused to take rivaroxaban, the treatment was stopped in three other patients: two with adverse effects and one with chronic iron-deficiency anemia. Conclusions: Rivaroxaban may represent an alternative for secondary thromboprophylaxis for thrombo-embolism in patients with APS, in particular, those with poor international normalized ratio (INR) control and those who are not at the highest risk of recurrent thrombosis, such as those with triple positivity.